1979
DOI: 10.1111/j.1600-0447.1979.tb00277.x
|View full text |Cite
|
Sign up to set email alerts
|

Symptom reduction in depression after treatment with L‐tryptophan or imipramine

Abstract: Thirty-eight in-patients with endogenous- and 20 in-patients with non-endogenous depression, took part in a multi-centre 3-week double-blind trial where patients were randomly allocated to treatment with either 6 g L-tryptophan or 150 mg imipramine daily. Item analysis of Hamilton ratings, before the investigation and weekly during the trial period demonstrated few statistically different mean scores on individual items between the two treatment groups. After 3 weeks' treatment a statistically significant item… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Bridges et al (1976) found that ventricular cerebospinal fluid L-tryptophan levels were already significantly higher in agitated compared to nonagitated psychiatric patients, so there is no theoretical justification for administering Ltryptophan to such patients. Accordingly, two clinical studies in depressed patients reported that agitation and anxiety were not significantly reduced by L-tryptophan (Herrington et al 1976;Lindberg et al 1979).…”
Section: Discussionmentioning
confidence: 99%
“…Bridges et al (1976) found that ventricular cerebospinal fluid L-tryptophan levels were already significantly higher in agitated compared to nonagitated psychiatric patients, so there is no theoretical justification for administering Ltryptophan to such patients. Accordingly, two clinical studies in depressed patients reported that agitation and anxiety were not significantly reduced by L-tryptophan (Herrington et al 1976;Lindberg et al 1979).…”
Section: Discussionmentioning
confidence: 99%
“…The severity of symptoms for all patients was assessed using the Japanese version of the 17-item Hamilton Depression Rating Scale (HAM-D) and the Beck Depression Inventory-II (BDI-II) on the day of the PET scan (19,20). All participants performed three neuropsychological tests: the Trail Making Test, parts A and B, and the Symbol Digit Modalities Test (21,22).…”
Section: Clinical and Neuropsychological Assessmentmentioning
confidence: 99%
“…Other studies supporting good reliability properties for the BPRS in different settings are summarized in a review article by Hedlund and Vieweg (1980). For the Hamilton Depression Scale, interrater reliability for the total scale has been shown to range from 0-78 to 0.96 (Bech et al, 1975(Bech et al, , 1979Cicchetti and Prusoff, 1983;Fava et al, 1982;Hamilton, 1960;Hodern et al, 1963;Kneseirch et al, 1977;Lindberg et a/., 1979;Maier and Philip, 1985;Miller, 1980;Rehm and O'Hara, 1985;Ziegler et al, 1978). Further evidence on reliability and other properties of the HDS are found in a review article by Hedlund and Vieweg (1979).…”
Section: Discussionmentioning
confidence: 99%